Monitoring and Managing Stress during Pregnancy with the ‘Smart Mother’ Information System for Early Detection - Runjati Runjati; Sri Rahayu; Arum Budiyati; Krisdiana Wijayanti; Mundarti; Rr Sri Endang Pujiastuti; Nur Abadi (Jurnal Kesehatan Masyarakat, 2026)
Psychological adjustment during pregnancy plays a vital role in maintaining maternal mental health and supporting fetal well-being. This study developed and evaluated Smart Mother, a smartphone based application designed for early detection and management of stress among pregnant women. The system was developed using the System Development Life Cycle (SDLC) framework and tested through a randomized controlled trial following CONSORT guidelines. A pretest–posttest design was conducted with 120 pregnant women randomly assigned to an intervention group (n = 60) and a control group (n = 60) from March to October 2023. The intervention group utilized the Smart Mother application, which integrates stress screening and self management features, while the control group received conventional printed educational materials. Statistical analysis using the Wilcoxon signed-rank test, Mann–Whitney U-test, and multivariate analysis showed a significantly greater reduction in stress scores in the intervention group compared with the control group (7.19 ± 5.8 vs. 5.87 ± 4.2; p< 0.01). Evaluation based on the Technology Acceptance Model (TAM) demonstrated high usability, with an average score of 4.26 (85.2%). These findings suggest that Smart Mother is an effective digital tool for improving stress monitoring and management during pregnancy and supports more comprehensive antenatal mental health care.